Is taxonomic homogenization linked to functional homogenization in temperate forests?. Issue 8 (6th March 2014) - Sonnier, Grégory; Johnson, Sarah E.; Amatangelo, Kathryn L.; Rogers, Dave A.; Waller, Donald M.
Abstract Aim Biotic homogenization – the tendency for communities to converge in species composition – has occurred in many ecosystems, creating management challenges. The extent to which this convergence in species composition is related to convergence in trait composition ('functional homogenization'), however, remains unresolved. Location North America, Wisconsin. Methods Using extensive plant community survey data from the 1950s and 2000s, and values for 11 traits measured on 169 species, we examined changes in functional beta diversity across 151 upland forest stands distributed across southern and northern Wisconsin. To estimate functional beta diversity, we used two recently developed pairwise functional dissimilarity metrics, plus an additive partitioning of functional diversity approach. Results Using pairwise functional dissimilarity metrics, we found no significant changes in functional beta diversity through time in either southern or northern upland forests. Under additive partitioning, species alpha diversity was lower than species beta diversity; whereas functional alpha diversity was much higher than functional beta diversity in both time periods and across all forest types. This suggests a high turnover of species but a low turnover of traits among communities. Main conclusions Although upland forests in Wisconsin have experienced taxonomic homogenization, they have not undergone functional homogenization, which may reflect a high functional redundancy among Wisconsin forest plants. As species decline further or disappear in response to habitat fragmentation and other global changes, functional redundancy may decline in a way that could diminish the functional diversity of Wisconsin's forests at both local and regional scales.